INCREASING STUDENTS' VOCABULARY SKILL USING LITERATURE: CLASSROOM ACTION RESEARCH AT MAN 1 PROBOLINGGO - Febrianti, Dila; Tirmidi, Tirmidi; Kaharudin, Utsman (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effectiveness and improvement of the skills of class XI Language students of MAN 1 Probolinggo through the application of a literature-based learning model, especially poetry. The main problem identified is the low learning outcomes of students' skills, which is indicated by the average Pre-cycle score of 62. This study is a Classroom Action Research (CAR) with a quantitative approach implemented in two cycles. Quantitative data was obtained from learning outcome tests which showed a significant increase in each cycle. After the intervention in Cycle I, the average student score increased to 74. Further improvement was achieved in Cycle II, with the average learning outcome reaching 86. These results prove that the use of poetry in a systematic and planned manner is effective in improving students' comprehension skills, enabling them to understand the context and nuances of word meanings more deeply, thus achieving the Minimum Completion Criteria (KKM).